The effect of the equivalent load distribution on the behaviour of a membrane modelling the reinforcement of a load transfer platform - Beata Gajewska; Marcin Gajewski (Acta Scientiarum Polonorum. Architectura)
The distribution of the equivalent load in the analysis of the reinforcement of an embankment load transfer platform on a soft soil reinforced with columns has an impact on the behaviour of the membrane modelling this reinforcement. Depending on the calculation model, triangular, uniform and inverse triangular distributions are commonly used. The paper analyses the behaviour of the membrane under the influence of 11 different load distributions. For all distributions, deflection curves and diagrams of tensile forces, deformation and the angle of rotation of the membrane were determined for the task of modelling the full-scale experiment. An analysis of the influence of the subgrade reaction modulus (k value) of the soft soil between the columns and the reinforcement stiffness on the membrane behaviour was also carried out. It was found that the adoption of one of the load distributions as suitable in every design situation is not always justified. As a result of the analyses, it has been shown that increasing soil stiffness (k value) significantly changes the nature of the function of deflection, deformation and normal force in the membrane, and this change depends on the distribution of the equivalent load.